Bigas Luna and the Being of Spain: A Reading of "Jamón, Jamón" (1992) - (:unkn) unknown (My University, 2016)
This thesis aims at seeing Bigas Luna’s Jamón, jamón (1992) as a modern text that explores the issue of the so-called Being of Spain. Although the Being of Spain has often been considered an issue constricted to the first half of the twentieth century (as well as centered around the question of which landscape could best express the essence of Spanishness), I want to add to the discourse that such an issue is not an issue that must be constricted temporarily to the first half of the twentieth century, but still a current one. In developing this topic, I will use two texts from writers of the Generation of 98: Ángel Ganivet’s Idearium español (1897), which praises Spain’s isolation from foreign influences in order to preserve Spanishness, and José Ortega y Gasset’s España invertebrada (1921), which asserts Spain’s need for openness to foreign, modernizing influences. This confrontation of viewpoints is visualized in Jamón, jamón, but with the particularity of not offering a dichotomy between a rural Spain and a modern Europe (which is what Ortega, Ganivet and most of the ‘98ers discussed), but between Spain, Europe and the new global market. These three spaces are embodied by the three male characters, Raúl, Manuel and José Luis, respectively. Alongside an analysis of the rich imagery which pervades the film, my claim in the thesis is that Luna envisions the preservation of Spanishness against the United States and the global neoliberal economy through a combination of both Ganivet’s and Ortega’s views. In other words, whereas Ganivet and Ortega offered opposing visions regarding the Being of Spain (isolation versus openness), Luna synthesizes both positions against a third agent (the openness to a global culture that depersonalizes and converts everything in commodities) that does not appear in the writers above. In this sense, my claim in the thesis is that the Being of Spain that Luna emphasizes in Jamón, jamón is an identity which only can be preserved within the European context because, only through the openness to Europe can Spain’s cultural specificity can be preserved. In addition to the texts from writers of the Generation of 98, I will utilize part of Benedict Anderson’s and Anthony Smith’s theoretical framework on nationalism. In addition to this, I will outline some of the contradictions that I find regarding this argument. Therefore, one of my main concerns in the thesis will be the analysis of the character of Manuel, probably the less studied male character of the movie by scholars, as well as the validity, today, of Bigas Luna’s argument that Europe comes to represent that location in which tradition and modernity can coexist peacefully –an argument that would be seen as impossible by Ganivet and Ortega. Therefore, it is my purpose to argue how Luna explores that confrontation between those three bodies as a metaphor of Spain’s resistance to modernity.
Keywords: ANGEL GANIVET; BEING OF SPAIN; BIGAS LUNA; IBERIAN TRILOGY; JOSE ORTEGA Y GASSET; SYMBOLISM